Rencana Tata Tanam Kelompok Tani Sumber Rejeki Kecamatan Durenan Kabupaten Trenggalek - Susanto, Didik; Nareswari, Aptika Hana Prastiwi; Ristiyawati, Asca; Rahardjo, Tjatur Prijo (JATIMAS : Jurnal Pertanian dan Pengabdian Masyarakat, 2023)
Community service in the farming environment is a concept that describes the active efforts of agricultural instructors and educators in making positive contributions to farming communities. This activity was carried out in the working area of the Sumber Rejeki Farmers Group, Durenan District, Trenggalek Regency, East Java. Target farmers will receive knowledge and implement best practices to increase agricultural productivity sustainably. The aim of preparing planting arrangements is to help with more efficient and sustainable agricultural planning by considering natural cycles and the characteristics of the plants to be cultivated. The planting plan was designed based on climate factors, temperature, rainfall and duration of sunlight. Plant characteristics were also an essential consideration in determining planting plans. Planting planning is an essential tool in modern agriculture because it will facilitate agricultural actors to plan and manage agriculture more effectively, increase productivity and maintain environmental sustainability. Integration between educators, agricultural extension workers and farmer groups provides tangible benefits for overcoming food problems and building solid foundations for sustainable agriculture. It also appreciates farmers' important role in maintaining communities' resilience and well-being. Pengabdian masyarakat di lingkungan petani merupakan konsep yang menggambarkan upaya aktif penyuluh pertanian dan tenaga pendidik dalam memberikan kontribusi positif kepada masyarakat tani. Kegiatan ini dilaksanakan di wilayah kerja Kelompok Tani Sumber Rejeki, Kecamatan Durenan, Kabupaten Trenggalek, Jawa Timur. Petani sebagai sasaran akan menerima pengetahuan dan melakukan praktik terbaik untuk meningkatkan produktivitas pertanian secara berkelanjutan. Penyusunan tata tanam bertujuan untuk membantu perencanaan pertanian yang lebih efisien dan berkelanjutan dengan memperhitungkan siklus alam dan karakteristik tanaman yang akan dibudidayakan. Rencana tata tanam dirancang berdasarkan faktor iklim, suhu, curah hujan, dan durasi sinar matahari. Karakteristik tanaman juga menjadi pertimbangan penting dalam menentukan rencana tata tanam. Rencana tata tanam adalah alat yang sangat penting dalam pertanian modern karena akan memfasilitasi pelaku pertanian untuk merencanakan dan mengelola pertanian lebih efektif, meningkatkan produktivitas, dan menjaga keberlanjutan lingkungan. Integrasi antara tenaga pendidik, penyuluh pertanian, dan kelompok tani memberikan manfaat nyata untuk mengatasi masalah pangan serta membangun fondasi kuat untuk pertanian berkelanjutan. Hal ini juga menghargai peran penting yang dimainkan oleh petani dalam menjaga ketahanan dan kesejahteraan komunitas.